"But I Never Thought I'd Teach the Little Kids": Secondary Teachers and Early-Grades Music Instruction. (September 2016) - Salvador, Karen; Corbett, Keith
Even in states with K–12 music licensure, not all music education students take a course in elementary music methods, and even fewer take a course that specifically addresses early childhood music instruction. In this article, a music teacher educator and a self-described "band guy, " who initially struggled to work with young children, present strategies and mindsets that evolved through coursework, coteaching episodes, and interviews. During these interactions, the former "band guy" developed not only into an effective music teacher for young children but also into someone who enjoys working with "the little kids." Adopting these strategies and mind-set could help music educators who struggle to work with young children, thus improving the quality of music instruction for children in the early elementary grades.